Management outcome of knee septic arthritis in neonates and infants:A systematic review - Hilmi Muhammad; Rahadyan Magetsari; Alfin Ihza Trimahendra; Paramita Ayu Saraswati (Journal of Orthopaedic Reports)
Introduction: Septic arthritis (SA) is considered an orthopedic emergency especially when occurring in infants yet the gold standard for its management is yet to be determined with only a scanty amount of research carried out the detailed outcomes information from different types of treatment used. This review identifies the detailed outcomes of infants with knee SA managed by various types of therapy. Material and methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards were used as guidelines in constructing this review. The study protocol was registered into the International Prospective Register of Systematic Reviews database prior to this review commencement (CRD42022379017). In October 2022, a thorough search was first conducted on PubMed, Cochrane Library, Scopus, and Web of Science. We focused on including findings with the population of interest being infants with knee SA who underwent various types of therapy consisting of surgical intervention and antibiotic administration with detailed outcomes. Results: A total of 14 articles were included, extracting detailed outcomes of infantile knee SA cases managed by different treatment choices. Only 3 articles reported the full information regarding the patient's outcomes where the patient's quality of life was the most reported information followed by range of motion and laboratory evaluation in 8 studies, and radiographic evaluation in 7 studies. Conclusion: Detailed patient outcomes and specific data regarding the patient's demographics including risk factors are needed to construct the guidelines for infantile knee SA for more uniform management consisting of surgical intervention and antibiotic administration with its duration.